TI-BEARING GABBROIDS OF PENISEVICHY ILMENITE ORE MANIFESTATION (VOLYNSKIY MEGABLOCK OF THE UKRAINIAN SHIELD) - MYTROKHYN, O.; MYTROKHYNA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Penisevichy ilmenite ore manifestation connected with the metagabbroic dike-like body within Fedorovka gabbro-anorthosite massif of Korosten complex has been investigated. The tectonic position of the ore manifestation, its mode of occurrence and the ore composition have been studied. It has been determined that the primary composition of the Ti-bearing metagabbrolds was the ilmenite-rich melanocratic norite. Authors concluded that the Penisevichy Ti-bearing gabbroids are similar to the Tellnes Ilmenite norites of Norway but differ from them by postmagmatic alteration that however did not affect on the ore matter redistribution. It is supposed that ilmenite enrichment taken place as early as magmatic stage.